2010
DOI: 10.4103/0971-3026.69358
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Cervical spinal cord signal changes in a case of adult-onset subacute sclerosing panenchephalitis

Abstract: In this article, we report a case of subacute sclerosing panencephalitis (SSPE) in which there were central cervical cord signal changes on MRI. The spinal cord is uncommonly involved in SSPE. However, demonstration of spinal cord signal change in a patient of SSPE has significant implications for the differential diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…described a similar case of SSPE in a young adult lady who had vision loss followed years later by myelopath. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…described a similar case of SSPE in a young adult lady who had vision loss followed years later by myelopath. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Such DW restriction has been described to be indicative of fulminant SSPE in a few case reports. [10,11] Involvement of spinal cord in SSPE is also rare, described only in few case reports [12][13] as cervical cord involvement. In our case, thoracic cord was involved with abnormal signal in the anterior and lateral cord.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological and immunological studies on autopsy cases have demonstrated the involvement of the spinal cord 13 14. A case of adult onset SSPE has been reported with cervical cord signal changes on MRI 15. Presence of spinal cord signal changes on MRI calls for extensive medical and laboratory diagnosis to rule out other diseases.…”
Section: Discussionmentioning
confidence: 99%